Aerobic oxidation of primary benzylic amines to amides and nitriles catalyzed by ruthenium carbonyl clusters carrying N, O-bidentate ligands. Issue 11 (27th February 2020) - Yan, Xinlong; Dong, Qing; Li, Ying; Meng, Lizhen; Hao, Zhiqiang; Han, Zhangang; Lu, Guo-Liang; Lin, Jin
Abstract : An efficient method for direct oxygenation of primary arylamines to nitriles and amides with switchable selectivity was developed using N, O-bidentate Ru3 clusters as catalysts. Abstract : Four trinuclear ruthenium carbonyl clusters, (6-BrPyCHRO)2 Ru3 (CO)8 (R = 4-OCH3 C6 H4, 1a ; R = 4-BrC6 H4, 1b ) and (2-OC6 H4 –HCN–C6 H4 R)2 Ru3 (CO)8 (R = 4-OCH3, 2a ; R = 4-Br, 2b ), were synthesized from the reactions of Ru3 (CO)12 with the corresponding N, O-bidentate ligands (two pyridyl alcohols and two Schiff bases) respectively in a ratio of 1 : 2. Three new complexes 1b, 2a and 2b have been fully characterized by elemental analysis, FT-IR, NMR and X-ray crystallography. The catalytic activity of these ruthenium complexes for the aerobic oxidation of primary benzylic amines to amides and nitriles in the presence of t -BuOK was investigated, of which the Schiff base complex 2a was found to exhibit the highest activity.